Development of comprehensive safety management assessment of liquefied petroleum gas stations in Suratthani, Thailand - Na Songkhla, Thitima (2018)
Liquefied Petroleum Gas (LPG) is a relatively popular automotive fuel in Thailand. Gas stations are hazardous workplaces. There have been incidents of leakage, fire and explosions. There are all enormous potential hazards to the people, communities, assets, the environment, and reputation of an operating company, for this reason there is a need to investigate the causes of incidents and assessment of emergency management in the LPG stations, to assess the risks for accidents of LPG station using accident modeling and analyzing consequences of hazards and emergencies based on the worst case scenario in a LPG station. The study revealed that most incidents in LPG stations were LPG releases and car collisions. There were some significant processes in which incidents occurred in LPG stations such as filling LPG from dispenser to customer car and loading from LPG road tanker to tank. The characteristics of incidents were equipment leakage from the customers and the equipment leakage from the station. The parts of equipment which failed or incidents occurred were the valves of customer equipment, the dispensers and the valves in the stations. Those incidents in LPG stations were caused by training, safety inspection, safety behavior of workers and customers, safety knowledge of customers and workers and safety management in LPG stations. Besides, accident modeling and risk analysis in LPG station calculated the probability of different occurrences and outcomes. The consequences of abnormal events including incidents, near misses their future probability of prevention barriers and consequences of each event were analyzed into the release prevention barrier (RPB), damage control and emergency management barrier (DC&EMB), dispersion prevention barrier (DPB), ignition prevention barrier (IPB) and fire escalation prevention barrier (FEPB) respectively. The probabilities of the consequences were included in the event sequence diagram occurrence: safe, near miss, minor accident, major accident, serious accident and catastrophic accident or disaster. Moreover, release prevention barrier (RPB) was a medium risk level. It was a significant risk that needs to be improved and controlled effectively. Furthermore, consequence analysis was based on the worst case in the LPG station, and the consequence that would occur in different scenarios would be the gas dispersion, flash fire, jet fire, fireball and overpressure or explosion. The worst case of the consequence was the LPG road tanker rupture. There were damage distances of 1,059.26 meters from the overpressure or explosion and concentration radius of which the hazard distance was 1,258.41 meters. Therefore, the longest distance or radius to impact people, assets and communities was more than 1,300 meters (1.3 km). It means that the hazard radius or hazard distance would damage the LPG station, hotels, shops, stores, companies, garages, residences, home centers, home goods stores, restaurants, cafes, automax, car shops and car centers around station inescapably.